The Accessibility, Satisfaction, and Long-Term Care Needs of Elderly Residents: A Diverse Infrastructure Model - Cong, Cong; Bo, Li Jing; Yuan, Wei; Liang, Huan (Journal of Humanities and Social Sciences Studies, 2025)
This research evaluated the accessibility, satisfaction, and long-term care needs of Beijing elderly residents with the aim of constructing a heterogeneous healthcare infrastructure model to meet the needs of an aging urban population. Utilizing a descriptive-correlational design, data were collected from 352 participants using validated questionnaires and were analyzed via descriptive statistics, Pearson correlation, and regression analysis. Findings indicated that there was strong satisfaction with chronic care and access, but moderate satisfaction with continuity of care, mental health support, and affordability. There was high correlation between elderly well-being, integrated services, and infrastructure adequacy. Based on Integrated Theory of Healthcare for Aging Populations and the Socio-Ecological Model, this study recommends a patient-centered, inclusive healthcare model that integrates medical, social, and emotional care. The research yields new policy and system reform information but is limited to a cross-sectional design and local setting. Longitudinal effects and technology-based interventions to promote overall aging in urban areas must be the targets of future research.